2021
DOI: 10.1177/17427150211055291
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing compassionate leadership from the case of Jacinda Ardern: Legitimacy, paradox and resource conservation

Abstract: During times of suffering such as that inflicted by the COVID-19 pandemic, compassion expressed by leaders helps to ease distress. Doing so, those in a position to provide resources that might facilitate coping and recovery are attentive to the situations of distress. Despite an abundance of leadership theorizing and models, there still is little academic literature on compassionate leadership. To address this limitation, we present an exploratory case study of New Zealand Prime Minister Jacinda Ardern, someon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 103 publications
2
12
0
Order By: Relevance
“…In considering different news platforms from different regions, I attempted to examine reports, stories, and interviews in major media houses such as National Public Radio, CNN, Reuters, BBC, DW, and Al Jazeera to represent voices and analysis from the North America, Europe/Germany, and the Middle East/Asia regions respectively. Similar to selection criteria used by Simpson et al, (2022), another reason for selecting these sources was their generally robust editorial policies and global credibility. This is not to say these outlets are immune to biases, but simply to clarify and emphasize that effort was made to collect information from entities generally considered to be reputable and dependable.…”
Section: Methodsmentioning
confidence: 99%
“…In considering different news platforms from different regions, I attempted to examine reports, stories, and interviews in major media houses such as National Public Radio, CNN, Reuters, BBC, DW, and Al Jazeera to represent voices and analysis from the North America, Europe/Germany, and the Middle East/Asia regions respectively. Similar to selection criteria used by Simpson et al, (2022), another reason for selecting these sources was their generally robust editorial policies and global credibility. This is not to say these outlets are immune to biases, but simply to clarify and emphasize that effort was made to collect information from entities generally considered to be reputable and dependable.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, Jacinda Ardern's communication can serve as a compass in assessing a leader's response to the global health crisis. Jacinda Ardern's approach is not free from criticism: Her strategy could be criticized as isolationist rather than fostering a global effort (Simpson et al, 2021). However, the Ardern-led approach enjoyed a high level of cross-party support and an overwhelming endorsement from the public, with an approval rating of over 80% throughout the initial stages of the Covid-19 pandemic, as compared to the 48% average approval rating among G7 countries (Colmar Brunton, 2020).…”
Section: Jacinda Ardern: Reframing Leadership Through Communication O...mentioning
confidence: 99%
“…(Ardern, 2020) Through her communication, Ardern carries out a unifying campaign that galvanizes the collective will to suspend the citizenry's day-to-day life temporarily in support of lockdown measures (Jamieson, 2020). Widely recognized for her compassionate leadership (Simpson et al, 2021), Jacinda Ardern's communication enables her followers' resources and alleviates their distress during the meta-crisis of the Covid-19 pandemic (Saccà & Selva, 2021). Her daily briefings focused on open, honest, and straightforward communication, distinctive and motivational language, and expressions of care, including her characteristic appeals to kindness (Beattie & Priestley, 2021).…”
Section: Jacinda Ardern: Reframing Leadership Through Communication O...mentioning
confidence: 99%
“…Based on the field findings and from the various research sources, which have gone through the data collection process as well as analysis, it is shown that the leadership of the North Luwu Regency Regent from the community's point of view is more caring, considerate, compassionate, and more protective (Khatimah, 2022;Lukman, 2020aLukman, , 2020bLukman, , 2021Lukman, , 2022aLukman, , 2022bUlandari et al, 2022). Based on the theory and a model of compassionate leadership (Binagwaho, 2020;Shuck et al, 2019;Simpson et al, 2022;West & Chowla, 2017), the Regent of North Luwu Regency deserves to be described as a leader who understands the feelings and suffering of her people and puts the interests of society first in difficult times such as the COVID-19 in North Luwu.…”
Section: Compassionate Leadership Governance and Legitimating Actionsmentioning
confidence: 99%